Current concepts in the diagnosis and management of exercise-induced bronchospasm - Parsons, J. P. (The Physician and Sportsmedicine, 2010)
Exercise-induced bronchospasm (EIB) is a common occurrence in individuals with asthma, though it can also affect individuals without asthma. It occurs frequently in athletes. Common symptoms include coughing, dyspnea, chest tightness, and wheezing; however, there can be a variety of more subtle symptoms. The differential diagnosis of EIB is broad and includes several pulmonary and cardiac disorders. During the initial evaluation, a complete history, physical examination, and spirometry should be performed. In most patients with EIB, the baseline spirometry is normal; therefore, bronchoprovocation testing is strongly recommended. Both pharmacologic and nonpharmacologic approaches are important in the treatment of EIB. Management of EIB on the sideline of athletic events requires preparation and immediate access to rescue inhalers.